The influence of work from home and work-life balance on job satisfaction mediated by work stress at the regional development planning agency (Bappeda) of South Tapanuli Regency - Sri Anggraeni Nasution; Hasrudy Tanjung (Economic: Journal Economic and Business, 2026)
This study examines the relationships between Work From Home (WFH), Work-Life Balance (WLB), and Job Satisfaction, with Work Stress acting as a mediating variable among employees of the Regional Development Planning Agency (Bappeda) of South Tapanuli Regency. A quantitative cross-sectional survey design was employed, involving the entire population of 72 employees through a saturated sampling approach. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that WFH was positively and significantly associated with Job Satisfaction, with a path coefficient of 0.267 and a p-value of 0.021, while WLB showed a positive and significant relationship with a coefficient of 0.341 and a p-value of 0.004. WFH and WLB were negatively associated with Work Stress, whereas Work Stress was negatively associated with Job Satisfaction. Work Stress partially mediated the relationships of WFH and WLB with Job Satisfaction, with indirect effects of 0.093 and 0.116, respectively. The model explained 71.2% of the variance in Job Satisfaction. These findings highlight the importance of flexible work arrangements, work-life balance, and effective stress management in supporting employee satisfaction in public-sector organizations.